2004
DOI: 10.1046/j.1464-5491.2003.01086.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of a high‐carbohydrate and a high‐monounsaturated fat, olive oil‐rich diet on the susceptibility of LDL to oxidative modification in subjects with Type 2 diabetes mellitus

Abstract: Natural food-based high-CHO and high-MUFA diets have similar effects on LDL oxidative resistance and metabolic control in subjects with Type 2 diabetes. A MUFA diet is a good alternative to high-CHO diets for nutrition therapy of diabetes because it also has a beneficial effect on the lipid profile and superior patient acceptance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
63
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(64 citation statements)
references
References 53 publications
0
63
0
Order By: Relevance
“…HDL cholesterol concentrations increased more with the LCD (+0.10 mmol/l, P = 0.002) in the study by Davis et al [7], yet no study reported any difference in HDL particle size. No study reported a greater improvement in total triglycerides at the final follow-up; however, VLDL triglycerides decreased more in the LCD over time (-0.12 mmol/l, P = 0.016) [20]. In the two studies that reported the total cholesterol/HDL ratio, the results were conflicting, with either no significant difference [12] or significant improvements in the LCD until 6 months (P = 0.044, diet 9 time) [17].…”
Section: Lipid Profilesmentioning
confidence: 97%
See 1 more Smart Citation
“…HDL cholesterol concentrations increased more with the LCD (+0.10 mmol/l, P = 0.002) in the study by Davis et al [7], yet no study reported any difference in HDL particle size. No study reported a greater improvement in total triglycerides at the final follow-up; however, VLDL triglycerides decreased more in the LCD over time (-0.12 mmol/l, P = 0.016) [20]. In the two studies that reported the total cholesterol/HDL ratio, the results were conflicting, with either no significant difference [12] or significant improvements in the LCD until 6 months (P = 0.044, diet 9 time) [17].…”
Section: Lipid Profilesmentioning
confidence: 97%
“…No difference between the two diets Nordman et al [34] Greater weight loss with LCD at 6 months but not 1 year Improved glycaemic control with LCD preferred were conflicting, with the one study reporting no difference [19], whereas another reported that people preferred the low-carbohydrate, high-monounsaturated diet [20].…”
Section: Additional Dietary Factorsmentioning
confidence: 99%
“…Additionally, replacement of carbohydrate and saturated fat with MUFAs led to a reduction in glucose and blood pressure and to an increase in HDL in patients with diabetes [36] . A MUFA-rich diet (40% of energ y as fat), also decreased VLDL cholesterol and VLDL triglycerol and was more acceptable to patients with non insulin-dependent diabetes mellitus (NIDDM) than was a higher carbohydrate diet (28% of energy as fat) [37] . A meta-analysis of studies in individuals with diabetes showed that a high fat diet with 22%-33% of the energy from MUFAs resulted in lower plasma total cholesterol, VLDL, and TG levels than did a low fat, high carbohydrate (49%-60% energy) diet [38] .…”
Section: Dietary Mufas and Nafld: Human Studiesmentioning
confidence: 99%
“…However, most of the conducted studies in human and animals confirmed the olive oil role in protecting against NAFLD, decreasing blood triglycerides, increasing high-density lipoprotein, reducing insulin resistance and hepatic steatosis [47][48][49][50][51]. It has showed that consumption of diets that rich in olive oil has a profound effect on different health outcomes, specially obesity, T2DM and metabolic syndrome [52].…”
Section: Journal Of Clinical Nutrition and Dietetics Issn 2472-1921mentioning
confidence: 99%